The Association of Long-Term Metformin Use with Cancer Risk in Type 2 Diabetes: A Systematic Review of the Evidence and Methodological Controversies - Satya Agung Nugroho; Hasnan Habib Affifudin; Rizkyta Audrey Candrasmurti (The Indonesian Journal of General Medicine, 2024)
INTRODUCTION: A substantial body of evidence suggests that type 2 diabetes mellitus (T2DM) is a systemic state that promotes carcinogenesis, with chronic hyperinsulinemia identified as a primary biological mechanism. Metformin, a first-line insulin-sensitizing agent for T2DM, has been investigated for potential anti-neoplastic properties due to its ability to reduce circulating insulin levels and exert direct cellular effects. However, the evidence is conflicting, with observational studies suggesting a protective effect while randomized controlled trials (RCTs) show null results. This systematic review synthesizes the evidence on the association between long-term metformin use and cancer risk in patients with T2DM and critically appraises the methodological controversies that complicate its interpretation. METHODS: A systematic review of key observational studies investigating the association between metformin use and cancer risk in T2DM patients was conducted. Included studies were of cohort and case-control design. The methodological quality of selected studies was assessed using the Newcastle-Ottawa Scale (NOS). Findings were synthesized for overall cancer incidence and mortality, site-specific cancer risks, and dose-duration relationships. A critical appraisal of potential biases, including time-related biases and confounding by comparator, was performed to contextualize the discrepancy between observational and RCT evidence. RESULTS: Observational studies and their meta-analyses consistently reported a significant reduction in overall cancer risk, with summary risk reductions of approximately 30-35% for both incidence and mortality. The strongest protective associations were observed for hepatocellular and pancreatic cancers. The evidence for colorectal and breast cancer was inconsistent, while the association with prostate cancer was weak. A clear dose- and duration-response relationship was a common finding, with benefits becoming significant only after several years of continuous use. In stark contrast, meta-analyses of RCTs have consistently found no association between metformin use and cancer incidence (RR 1.07; 95% CI, 0.87–1.31). Critical appraisal of the observational literature revealed a high potential for methodological flaws, particularly immortal time bias and confounding by comparison to potentially harmful agents (e.g., sulfonylureas), which may account for this discrepancy. DISCUSSION: The evidence regarding metformin's chemopreventive effect is defined by a fundamental conflict between a large body of observational data suggesting a strong protective effect and null findings from RCTs. The magnitude of risk reduction in observational studies is likely an overestimation driven by systematic biases. If a true protective effect exists, it is probably far more modest than initially reported and likely mediated by the systemic reduction of hyperinsulinemia, primarily affecting insulin-sensitive tumors. The alternative hypothesis—that metformin appears protective because it is often compared to agents like sulfonylureas that may increase cancer risk—cannot be dismissed. CONCLUSION: Observational studies and their meta-analyses consistently reported a significant reduction in overall cancer risk, with summary risk reductions of approximately 30-35% for both incidence and mortality. The potential for a modest reduction in the risk of certain cancers is a compelling hypothesis, but definitive conclusions await the results of large-scale, long-term RCTs designed with cancer as a primary endpoint.